Pemanfaatan Serasah Daun Bambu Menjadi Pupuk Organik di Desa Alu Kabupaten Polewali Mandar - Karim, Faradilah Farid; Indhasari, Fitri; Idris, Andi Irmayanti; Arhim, Muhammad (Jurnal Ilmiah Pangabdhi, 2023)
Alu Village is one of the villages in Polewali Mandar Regency, West Sulawesi Province. Alu Village has a bamboo forest covering an area of 18 ha. The existence of bamboo plants in Alu Village is very abundant, so bamboo leaf litter has the potential to be used as organic fertilizer. Most of the people of Alu Village make their living as farmers. Utilizing bamboo leaf litter into compost is a good alternative for the community. However, the lack of public knowledge regarding making compost means that many are still reluctant to use this fertilizer. This community service program aims to educate the public regarding the use of bamboo litter as compost and minimize bamboo litter waste in Alu Village. The method used is direct provision of materials and practice of making organic fertilizer from bamboo litter through the participation of active participants. The use of bamboo leaf litter as fertilizer, apart from utilizing waste, is also expected to have an influence on plant growth on agricultural land and plantations in local communities.